(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The researchers have found that the role of teachers in the teaching learning process is very important. Updated curriculum, advance books, tech enabled class room may fail in the absence of a committed teacher. The researchers have believed that a study on teachers will be very meaningful for improving the teaching learning processes. But there are several aspects related with teachers that contribute to the teaching learning process. The researcher, in the present research paper, have detailed Job satisfaction issues related with teachers and teaching learning process in India. A comparison among the private school teachers and government school teachers suggested that there is higher level of Job satisfaction among the teachers in government schools.